Quality of Life for Adult Clients with Hypermobility Syndrome Attending Private Clinics in Baghdad City: A Cross-Sectional Study - hasan, aqeel; Abdulwahd, hala (Iraqi National Journal of Nursing Specialties, 2019)
Objective)s): To evaluate the quality of life for adult clients with hypermobility syndrome at private clinics in Baghdad City. Methodology: A cross-sectional study used a purposive ‘’non-probability’’ sample of (75) adult clients with Hypermobility Syndrome (HMS) male and female who age (25-64) years. The data were collected through the utilization of standard developed questionnaire of the world health organization (WHO). Data collected by interview with each client who is involved in the study. Each interview takes approximately (20) minutes. Results: The study revealed that there is an effect of hypermobility syndrome on the quality of life, which recorded fair level in general. The study also reported that there is an effect of the condition on their physical, social and psychological domains. Recommendation: The study recommends that early diagnosis of hypermobility syndrome is essential to recognize and increase knowledge about condition for clients and their families, and that consultation and health education programs can help to prevent and minimize symptoms and raise the level of quality of life.